Efficacy and duration of analgesia with levobupivacaine combined with fentanyl or dexmedetomidine in lower extremity surgery: A meta-analysis - Mohit Gupta; Rana Pratap; Gajendra Pal Singh (Asian Journal of Medical Sciences, 2025)
Background: In combination with local anesthetics such as levobupivacaine, fentanyl, and dexmedetomidine improve post-operative analgesia after surgery on the lower extremities. Aims and Objectives: To determine whether the local anesthetic levobupivacaine in combination with fentanyl or dexmedetomidine can improve the efficacy and duration of analgesia in lower extremity surgery. Materials and Methods: After a search in PubMed, Google, and Web of Science, six randomized controlled trials with 400 patients were found. Review Manager 5 was then used to retrieve the study results and calculate the effect sizes. Results: The effects of 0.5% levobupivacaine with fentanyl (group F) and dexmedetomidine (group D) on sensory blockade, regression, and post-operative analgesia were investigated in numerous studies. Group D had a significant advantage in sensory regression (standard mean difference [SMD] −3.34, confidence interval [CI] [−4.07, −2.62], P<0.00001), although there was no significant difference in the onset of sensory blockade (SMD −0.21, CI [−1.28, 0.86], dexmedetomidine prolonged post-operative analgesia (SMD −7.34, CI [−11.08, −3.60], P=0.0001). The heterogeneity between the studies was substantial (I²=59–97%). The methodological excellence of the selected studies was reflected in their low risk of bias in all areas. Conclusion: Despite the identical onset of sensory blockade, dexmedetomidine prolongs sensory regression and post-operative analgesia more than fentanyl. Despite considerable variability, these results are supported by a low bias, making dexmedetomidine a better adjuvant for analgesia in chronic lower extremity surgery.